FAMILY KNOWLEDGE AND PREPAREDNESS IN FACING FLOOD DISASTERS IN BENGKULU CITY - Juksen, Loren; Elvira, Yulita; Fitriani, Desi; Rahmawati, Ida (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Floods are natural events that can occur at any time and often result in loss of life and property. Losses due to flooding can be in the form of damage to buildings, loss of valuables, so that the losses that result cannot be prevented, but can be controlled and reduced the impact of losses caused. Objectives: This study aims to determine the relationship between family knowledge and preparedness in facing flood disasters in Bengkulu City. Methods: This study used a cross-sectional research design. The population were head of family, samples obtained by accidental sampling technique as many as 90 respondents. Data analysis used univariate and bivariate analysis, questionnaire were knowledge and preparedness questionnaires Results: The results of this study showed that from 90 samples of family knowledge about flooding, 30 respondents (33.3%) were well informed and 44 respondents (48.9%) were well-knowledge, while 20 respondents (22.2%) had good preparedness, and 70 respondents (77.8%) had sufficient preparedness. The results of the Chi-square analysis obtained there was no significant relationship between family knowledge and preparedness Conclusion: The result of this research can be used as information material for the family that are about that the knowledge is not one of the factors can be affecting the preparedness of respondents in facing flood disaster.